Pilot test of environment-friendly catalysts for the DeNOx of low-temperature flue gas from a coal-fired plant. Issue 9 (25th March 2021) - Guo, Lin; Lu, Jianjiang; Zhao, Yonggang; Wang, Chengzhi; Zhang, Cheng; Tang, Changjin; Dong, Lin; Kong, Wei; Li, Qijun; Cao, Peng
Abstract : This figure reflects the process flow diagram of low-temperature SCR DeNO x and the test efficiency of 3400 h. Abstract : Efficient, environment-friendly, and energy-saving low-temperature denitration (DeNO x ) catalysts, applicable in practical flue gas, have a widespread market for use in small-scale boilers. A novel Ce-based low-temperature honeycomb catalyst was tested in a pilot-scale plant for DeNO x of flue gas from a coal-fired power plant. The pilot test results demonstrated the honeycomb catalyst's ability to endure a high content of water vapor (H2 O, 8–10 vol%) and low content of sulfur dioxide (SO2, ≤35 mg m −3 ) in flue gas at temperatures as low as 100 °C, with >55% DeNO x efficiency over 3400 h and the catalyst showed no deactivation. Physicochemical properties of the catalyst were investigated by various characterization methods, such as Brunauer–Emmett–Teller analysis, X-ray diffraction analysis, inductively coupled plasma, temperature-programmed desorption of NH3, thermogravimetry, and Fourier-transform infrared spectroscopy. The results showed the effectiveness of the selective catalytic reduction unit in preventing the deposition of particulate matter in the flue gas, after being placed in the desulfurization and dust removal unit. However, a small amount of alkali metal and sulfate deposition were detected on the surface and micropores of the catalyst but did not significantly impact the catalyst performance. This catalyst thus has broad potential applicability in actual flue gas.